Alterations in Blood–Brain Barrier Integrity and Lateral Ventricle Differ in Rats Exposed to Space Radiation and Social Isolation - Austin M. Adkins; Zachary N. M. Luyo; Alayna J. Gibbs; Alea F. Boden; Riley S. Heerbrandt; Justin D. Gotthold; Richard A. Britten; Laurie L. Wellman; Larry D. Sanford (Life, 2024)
The proposed Mars missions will expose astronauts to long durations of social isolation (SI) and space radiation (SR). These stressors have been shown to alter the brain’s macrostructure and microenvironment, including the blood–brain barrier (BBB). Breakdown of the BBB is linked to impaired executive functions and physical deficits, including sensorimotor and neurocognitive impairments. However, the precise mechanisms mediating these effects remain unknown. Additionally, the synergistic effects of combined exposure to SI and SR on the structural integrity of the BBB and brain remain unknown. We assessed the BBB integrity and morphology in the brains of male rats exposed to ground-based analogs of SI and SR. The rats exposed to SR had enlarged lateral ventricles and increased BBB damage associated with a loss of astrocytes and an increased number of leaky vessels. Many deficits observed in SR-treated animals were attenuated by dual exposure to SI (DFS). SI alone did not show BBB damage but did show differences in astrocyte morphology compared to the Controls. Thus, determining how single and combined inflight stressors modulate CNS structural integrity is crucial to fully understand the multiple pathways that could impact astronaut performance and health, including the alterations to the CNS structures and cell viability observed in this study.